2009
DOI: 10.1182/blood-2009-04-215525
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage (ICH) in children with immune thrombocytopenia (ITP): study of 40 cases

Abstract: Intracranial hemorrhage (ICH) is a rare but devastating complication of childhood immune thrombocytopenia purpura (ITP). A survey of ICH from 1987 to 2000 identified cases of ICH in childhood ITP in the United States. Forty patients with ICH and 80 matched ITP control subjects were accrued. The estimated incidence of ICH was 0.19% to 0.78%. Platelet counts were less than 20 ؋ 10 9 /L in 90% and less than 10 ؋ 10 9 /L in 75% of children with ICH. Eighteen (45%) children developed ICH within 7 days of diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
154
3
23

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(191 citation statements)
references
References 28 publications
8
154
3
23
Order By: Relevance
“…Previous research in children with ITP identified gross/microscopic hematuria as being potentially associated with risk of ICH [5]. Our findings suggest that microscopic hematuria is much more frequent (27% in our case series) than previously speculated in children with ITP, even when compared with healthy children.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Previous research in children with ITP identified gross/microscopic hematuria as being potentially associated with risk of ICH [5]. Our findings suggest that microscopic hematuria is much more frequent (27% in our case series) than previously speculated in children with ITP, even when compared with healthy children.…”
Section: Discussionsupporting
confidence: 48%
“…While hematuria (occult or overt) and other noncutaneous hemorrhage has been described as being associated with ICH [5], to our knowledge no prior studies have specifically investigated the frequency or clinical relevance of occult hemorrhage in ITP. The results of this study demonstrate that on average nearly 27% of children with severe ITP, defined as thrombocytopenia 10,000/mm 3 , have occult bleeding demonstrable in the urinary tract and that such bleeding is more common than overt symptomatic hematuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major bleeding, including spontaneous intracerebral haemorrhage, occurs predominantly in patients with platelet counts <20×10 9 /L, generally <10×10 9 /L [16,17]. Haemorrhagic complications may be more common in patients older than 60 years of age and those with comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…3 Severe bleeding is a rare complication of ITP, with the incidence of intracranial hemorrhage ranging from 0.1% to 1%. [4][5][6] Other severe bleeding manifestations can present as epistaxis, gastrointestinal bleeding, menorrhagia, and hematuria. 7 Since ITP resolves spontaneously in most children, treatment is controversial; however, in children in children requiring therapy due to severe thrombocytopenia or bleeding, the 3 standard treatments include intravenous anti-D immune globulin, intravenous immunoglobulin G (IVIG), and steroids.…”
Section: Introductionmentioning
confidence: 99%